2018
DOI: 10.1161/hypertensionaha.118.10934
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Neuroinflammation in the Pathogenesis of Monocrotaline-Induced Pulmonary Hypertension

Abstract: Pulmonary hypertension (PH) is a devastating disease and its successful treatment remains to be accomplished despite recent advances in pharmacotherapy. It has been proposed that PH be considered as a systemic disease, rather than primarily a disease of the pulmonary vasculature. Consequently, an investigation of the intricate interplay between multiple organs such as brain, vasculature, and lung in PH could lead to the identification of new targets for its therapy. However, little is known about this interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 25 publications
(33 reference statements)
10
47
0
Order By: Relevance
“…It is associated with a variety of pathological disorders including neurotransmitter changes, disordered angiotensin levels, impaired endothelial functions, and overexcited sympathetic nerves as well as other processes such as inammatory factors and oxidative stress. [31][32][33] OA has a signicant antihypertensive effect on hypertensive animals, and its antihypertensive mechanism mainly involves the inhibition of vascular smooth muscle cell proliferation and inammation of the blood vessel wall, thus reducing blood vessel stenosis caused by balloon catheter injury and other causes. [34][35][36] Despite extensive studies, its mechanism associated with neuropathology remains completely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with a variety of pathological disorders including neurotransmitter changes, disordered angiotensin levels, impaired endothelial functions, and overexcited sympathetic nerves as well as other processes such as inammatory factors and oxidative stress. [31][32][33] OA has a signicant antihypertensive effect on hypertensive animals, and its antihypertensive mechanism mainly involves the inhibition of vascular smooth muscle cell proliferation and inammation of the blood vessel wall, thus reducing blood vessel stenosis caused by balloon catheter injury and other causes. [34][35][36] Despite extensive studies, its mechanism associated with neuropathology remains completely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The literature also indicated that a dysfunctional hypothalamic paraventricular nucleus was not only integral to some other physiological diseases, but was also likely caused by localised neuro-inflammation from overactive glial cells. [20][21][22] Might this circuitry be jolted into dysfunction by the triggers of the disease, thereby initiating a neuro-inflammatory response within the brains of ME/CFS patients? Then, neuroinflammation (and ME/CFS itself) could then be Figure 1).…”
Section: Onset Explainedmentioning
confidence: 99%
“…More than 70% of heritable and 20% of idiopathic PH cases have the BMPR2 gene mutations. Recent studies have found that in ammation is thought to be strong trigger factors and promotes the development of PH in Bmpr2 +/mice, in ammatory play an important role in PAH [7][8][9], in ammatory factors was signi cantly increased in clinical PH patient. In ammatory mediator tumor necrosis factor-α (TNF-α) could further promote the development of PH by reducing BMPR2 expression in PASMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Scutellaria baicalensis Georgi (huang qin) is a widely used herb in traditional Chinese medicinal herbs. The study found that baicalin has several biological effects including antioxidant, anti-in ammatory, antiviral, neuroprotective, anxiolytic, and anti-cancer activities [9][10][11][12][13]. Our previous study showed that baicalin could inhibit in ammatory, improve PH vascular remodeling and right ventricular impairment in monocrotaline (MCT)-induced experimental [14,15].…”
Section: Introductionmentioning
confidence: 99%